Reconsidering Self-Portraits by Women Surrealists: A Case Study of Claude Cahun and Frida Kahlo - Josten, Jennifer (Atlantis, 2006)
Both Claude Cahun and Frida Kahlo were affiliated with the Surrealist movement in the 1930s for political and professional ends. In their respective bodies of self-portraiture, they mirrored or doubled their own images and stretched the boundaries of gender and sexual representation in order to challenge heteronormative conceptions of identity.